Late onset vitreoretinal complications of regressed retinopathy of prematurity. Issue 2 (21st January 2004) - Tufail, A; Singh, A J; Haynes, R J; Dodd, C R; McLeod, D; Charteris, D G
Abstract : Aim: To report the clinical findings, management, and outcomes in eyes undergoing surgery for regressed retinopathy of prematurity (ROP) with vitreoretinal complications. Method: Retrospective review of 40 eyes of 32 patients with regressed ROP who presented between 1989 and 2001 at two UK referral centres. Results: Of 29 eyes presenting with rhegmatogenous retinal detachment (RRD), 15 initially underwent a scleral buckling procedure and 14 initially underwent vitrectomy with or without additional buckling. Primary surgery was anatomically successful in 11/15 eyes that underwent a non-vitrectomy retinal detachment repair and 8/14 that required vitrectomy. The final reattachment rate after reoperation was 28/29 eyes. Median visual acuity improved from 6/60 to 6/36 following retinal detachment repair. A further 11 eyes of eight patients from this series underwent prophylactic surgery, laser, or cryotherapy for predisposing vitreoretinal pathology and/or retinal breaks, all of which were stabilised. Conclusions: In eyes with RRD and signs of regressed ROP successful reattachment of the retina can be achieved using either vitrectomy or external surgery with an associated overall improvement in visual acuity. A range of external and closed microsurgical approaches is required to effectively deal with the diverse manifestations of regressed ROP.